Characterisation of the Colour Fraction of Pedro Ximenez Andalusian Sweet Wines - Serratosa, M.P.; Lopez-Toledano, A.; Medina, M.; Merida, J. (South African Journal of Enology and Viticulture, 2011)
Changes in colour fraction of commercially bottled Pedro Ximenez sweet wines, unaged and oxidatively aged in American oak casks and mostly produced in the Montilla-Moriles and Jerez-Xérès-Sherry Designations of Origin (Spain), have been studied. The total tannin content and the total polyphenol content (A280) increased with increased aging time, a trend clearly observed in the Jerez wines. Browning, as measured by the absorbance at 420 nm, differed markedly between unaged and aged wines. Aged wines showed an increase in browning with time and an increase in high molecular weight browning compounds, most probably Maillard compounds. Colour measurements based on the CIELab system showed a gradual decrease in hue and lightness with ageing.